Attaining Nationally Determined Contributions of Bangladesh through Greenhouse Gas Emission Reduction: Role of Solar PV Systems (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The paper analyzes as to how Bangladesh can secure its future demand of electricity and mitigate greenhouse gas emission to meet the targets of Nationally Determined Contributions (NDCs). The overall objective of the study is to assess the possible mitigation of greenhouse gases emission for achieving NDCs from power sector of Bangladesh through solar photovoltaic systems. A quantitative analysis was done to project future power consumptions and greenhouse gas emissions up to 2030. A scenario analysis was also done to see the effects of different primary energy mix in power on the emissions. It is found that the total consumption in different sectors will increase with an increasing population and the GDP. Industrial and residential sectors are the main consumers of power. The scenario result shows that there is relationship between the energy mix and greenhouse gas emissions. The fossil fuels have higher emissions in the scenarios where they are thought to be main contributor to the energy mix. In case of high renewables, the emissions can be mitigated to meet the targets of NDCs. As Bangladesh receives high solar radiation, grid-connected solar photovoltaic systems can be the main source of renewable energy in such case. Therefore, solar photovoltaic technology is essentially required not only for achieving the targets of NDCs but also for the development of a low carbon power sector in Bangladesh for a sustainable future.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 43-51